2017
DOI: 10.1177/0003489416685321
|View full text |Cite
|
Sign up to set email alerts
|

Surgery of Anterior Skull Base Lesions in Children

Abstract: Congenital pathologies of the anterior skull base are rare, challenging to diagnose, and present as clinical emergencies. An interdisciplinary surgical approach is needed for best functional and aesthetic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In a case series of 13 children with anterior skull base congenital lesions who underwent transnasal, transcutaneous, and/or transcranial surgical intervention, no postoperative morbidity or mortality was reported. 22 Other studies estimated an incidence of 2.9% for minor postoperative complications, while major complications occurred at a rate of 0.08% to 0.55%. 2,6,17 In a retrospective review of nationwide data for inpatient and outpatient sinus surgery, Ramakrishnan et al 17 reported complication rates by age.…”
Section: Discussionmentioning
confidence: 97%
“…In a case series of 13 children with anterior skull base congenital lesions who underwent transnasal, transcutaneous, and/or transcranial surgical intervention, no postoperative morbidity or mortality was reported. 22 Other studies estimated an incidence of 2.9% for minor postoperative complications, while major complications occurred at a rate of 0.08% to 0.55%. 2,6,17 In a retrospective review of nationwide data for inpatient and outpatient sinus surgery, Ramakrishnan et al 17 reported complication rates by age.…”
Section: Discussionmentioning
confidence: 97%
“…The differential diagnoses in our patient included nasal glioma, encephalocele, congenital hemangioma, sebaceous cyst, and lipoma [ 5 , 8 ]. A nasal glioma is an ectopic, neuroectoderm from early development that presents as a firm, noncompressible, flesh-colored nodule.…”
Section: Discussionmentioning
confidence: 99%
“…The pediatric population presents challenges from small surgical corridors to non-pneumatized sinuses [25]. The approach has been expanded to include younger patients and additional pathology including Rathke cleft cysts, pituitary adenomas, arachnoid cysts, craniopharyngioma, and other less common lesions [34][35][36][37]. The effect of pediatric EES on long-term midface growth is still unclear.…”
Section: Discussionmentioning
confidence: 99%